EKSISTENSI NILAI-NILAI NASIONALISME PENINGGALAN MOHAMMAD HATTA DAN SUTAN SJAHRIR DI PULAU BANDA - Asriana Yanto; Louisa Metekohy; Susi Anita Patmawati (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
This study aims to analyze the existence of the values of nationalism left behind by Mohammad Hata and Sultan Sjahrir on Banda Island. The importance of nationalism values for the Indonesian nation, the nationalism values that need to be instilled include love for the homeland, willingness to sacrifice, pride in diverse cultures, appreciation for the services of heroes, and prioritizing the public interest. Connecting the past and emphasizing the nationalism values instilled through history and their relevance in the era of disruption, directly connecting the importance of preserving the traces of heroes with the formation of the nation's character. The type of research is qualitative. The research location is Banda Island, Central Maluku Regency, Maluku Province. The subjects of this research are the community responsible for maintaining the Cultural Heritage Site or the managers of the exile house, traditional leaders, community leaders, and the people of Banda Naira. The data collection techniques are observation and documentation. The data is analyzed using descriptive qualitative methods. The research results show that the values of nationalism contained in the historical traces of Mohammad Hatta and Sutan Sjahrir on Banda Island are reflected through their attitudes, thoughts, and activities during their exile. Translated with DeepL.com (free version) These values include love for the homeland, fighting spirit, sacrifice, unity, and efforts to educate the public through education and intellectual enlightenment. The historical traces left behind are proof of the existence of the nationalist values of these two figures. The preservation and utilization of the historical relics of Mohammad Hatta and Sutan Sjahrir on Banda Island play an important role in shaping the historical awareness and nationalism of the community. These historical relics not only serve as historical evidence, but also as a means of education and learning that can foster a love for the homeland and pride in the nation's history. ABSTRAK Penelitian ini bertujuan untuk menganalisis eksistensi nilai-nilai nasionalisme peninggalan Mohammad Hata dan Sultan Sjahrir di Pulau Banda. Pentingnya nilai-nilai nasionalisme bagi bangsa Indonesia, Nilai-nilai nasionalisme yang perlu ditanamkan antara lain cinta tanah air, rela berkorban, bangga pada budaya yang beragam, menghargai jasa para pahlawan serta mengutamakan kepentingan umum. menghubungkan masalalu dan penekanan pada nilai-nilai nasionalisme yang ditanamkan melalui sejarah dan relevansinya di era disrupsi, secara langsung menghubungkan pentingnya pelestarian jejak pahlawan dengan pembentukan karakter bangsa, Tipe dalam penelitian ini adalah kualitatif. Lokasi penelitian pada Pulau Banda, Kabupaten Maluku Tengah, Provinsi Maluku Subjek dalam penelitian ini adalah masyarakat yang bertanggung jawab menjaga Cagar Budaya atau pengelola rumah pengasingan, tokoh adat, tokoh masyarakat, serta masyarakat Banda Naira. Teknik pengumpulan data adalah observasi dan Dokumentasi. Data dianalisis secara deskriptif kualitatif. Hasil Penelitian bahwa Nilai-nilai nasionalisme yang terkandung dalam jejak-jejak sejarah Mohammad Hatta dan Sutan Sjahrir di Pulau Banda tercermin melalui sikap, pemikiran, dan aktivitas mereka selama masa pengasingan. Nilai-nilai tersebut meliputi cinta tanah air, semangat perjuangan, pengorbanan, persatuan, serta upaya mencerdaskan masyarakat melalui pendidikan dan pencerahan intelektual. Jejak sejarah yang ditinggalkan menjadi bukti eksistensi nilai-nilai nasionalisme kedua tokoh tersebut. Pelestarian dan pemanfaatan peninggalan sejarah Mohammad Hatta dan Sutan Sjahrir di Pulau Banda memiliki peran penting dalam membentuk kesadaran sejarah dan nasionalisme masyarakat. Peninggalan sejarah tersebut tidak hanya berfungsi sebagai bukti sejarah, tetapi juga sebagai sarana edukasi dan pembelajaran yang dapat menumbuhkan rasa cinta tanah air serta kebanggaan terhadap sejarah bangsa.